EFEKTIVITAS PEMBERIAN JUS BUAH NAGA TERHADAP PENINGKATAN KADAR HEMOGLOBIN REMAJA PUTRI DI SMPN 6 BATAM - Desfita S, Mely; Yunita, Prasida; Juni Ekasari, Dian (Universitas Batam, 2025)
Anemia is a medical condition hemoglobin is less than normal limits. In the world, the prevalence of anemia is 37%. Indonesia, 33.7% of adolescent girls suffer from anemia. Lack of micronutrients such as iron can cause anemia. Red dragon fruit (Hylocereus polyrhizus) is one of the fruits that is believed to increase hemoglobin. This fruit contains organic acids, protein, minerals such as potassium, magnesium, calcium and iron as well as vitamin C. This research aims to determine the effectiveness of giving dragon fruit juice on increased hemoglobin levels in adolescent girls. Quasi-experimental research design with one group pre-test and post-test design. The research was conducted at SMPN 6 Batam in April - July 2024 with a population of all VIII female students at SMPN 6 Batam in 2024 totaling 193. With a sample of 22 respondents taken by purposive sampling. Univariate and bivariate data analysis using SPSS. The research results showed that the mean HB level before the intervention was 10.91 and after the intervention of giving dragon fruit juice was 11.59. P value = 0.000 (α < 0.05), which means that statistically there is a significant difference in mean before and after giving dragon fruit juice, so it can be concluded that giving dragon fruit juice is effective in increasing hemoglobin levels in young women. It is hoped that young women can increase awareness of maintaining their dayly nutrition, and dragon fruit can be used as an alternative fruit that can be consumed to provide sufficient iron. Keywords: Dragon fruit, Hemoglobin, Teenage Girls